1995
DOI: 10.1002/j.2161-0045.1995.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Retirement: Role Changes and Psychological Resources

Abstract: In this review, the influence of social and work roles are incorporated into a model of retirement adjustment, along with two psychological moderators that may aid the retirement transition. These psychological resources, locus of control and retirement self-efficacy, are those behavioral predispositions that would lead one to engage in proactive strategies for mastering the role changes inherent in the retirement transition. The implications of social and work-related role changes and psychological resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
7

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 44 publications
4
87
0
7
Order By: Relevance
“…De acordo com a literatura, relacionamentos conjugais de qualidade operam como recursos positivos para um ingresso bem-sucedido na fase da aposentadoria (Carter & Cook, 1995;Floyd et 1992; Leandro-França et al, 2014a). Segundo os autores, ter vínculos familiares menos estabelecidos dificulta a transição, a adaptação e a capacidade de obter satisfação no momento da aposentadoria, uma vez que o círculo familiar e de amigos passa a ser a maior fonte de estímulos sociais após a saída do trabalho.…”
Section: Discussionunclassified
“…De acordo com a literatura, relacionamentos conjugais de qualidade operam como recursos positivos para um ingresso bem-sucedido na fase da aposentadoria (Carter & Cook, 1995;Floyd et 1992; Leandro-França et al, 2014a). Segundo os autores, ter vínculos familiares menos estabelecidos dificulta a transição, a adaptação e a capacidade de obter satisfação no momento da aposentadoria, uma vez que o círculo familiar e de amigos passa a ser a maior fonte de estímulos sociais após a saída do trabalho.…”
Section: Discussionunclassified
“…The authors argue that personal factors such as self efficacy and a sense of coherence in coping with the transition are important moderators in adjusting to retirement life. Carter & Cook (1995) add that a perception of feeling to be in control is a behavioural predisposition that would lead one to engage in proactive strategies for role changes in retirement transition. Towards this end, those who prepare psychologically for retirement view the event more positively and adjust better than those who enter retirement when they are unprepared.…”
Section: Psychological Factors and Retirementmentioning
confidence: 99%
“…Price and Bruchey (1998) In older adults, an intemallocus of control (belief in one's ability to control outcomes) has been associated with more positive coping strategies in the face of 28 challenging life events (Abel & Hayslip, 1986), including the four phases of retirement adjustment defined by Price and Bruchey (1998). For example, an internal locus of control was found to be an important psychological moderator in adjusting to the intrinsic role change which accompanies retirement transition adjustment (Carter & Cook, 1995). Similarly, a predisposition toward self-efficacy (the belief that one has the necessary skills and knowledge to effect control) was found to be an important predictor of retirement adjustment (Carter & Cook, 1995;Taylor & Shore, 1994).…”
Section: Retirement Adjustment and Personal Controlmentioning
confidence: 99%
“…For example, an internal locus of control was found to be an important psychological moderator in adjusting to the intrinsic role change which accompanies retirement transition adjustment (Carter & Cook, 1995). Similarly, a predisposition toward self-efficacy (the belief that one has the necessary skills and knowledge to effect control) was found to be an important predictor of retirement adjustment (Carter & Cook, 1995;Taylor & Shore, 1994). Two studies, however, found that locus of control had minimal effects on retirement adjustment (Hale, Hedgepeth &Taylor, 1985-86, andSherman, 1986).…”
Section: Retirement Adjustment and Personal Controlmentioning
confidence: 99%